The effects of the Minim Program of Prosocial Improvement on a high school students sample - Romersi, Silvia; Martínez Fernández, J. Reinaldo; Roche, Roberto (Anales de Psicología / Annals of Psychology, 2010)
This paper presents the core elements of prosocial behaviour that justify the interest in a 12-session intervention programme in high school (PMIP: Programa Mínimo de Incremento Prosocial - Roche, 2002). In the design and application of this programme, it is assumed that increasing the quantity and quality of prosocial actions has an effect on preventing aggressive and antisocial behaviours and improves the emotional education and the social climate on class. The aim of the study was to analyse the effects of PMIP in secondary school students. The participants are 198 students from six schools in the province of Barcelona (Spain) with an average age of 14.49 years old (SD= 0.80; range 14 till 16) and 53.% percent of women. The students were intentional assigned into experimental (n= 128) or control group (n= 70) according to Direction of the participant school. It was realize a one-factorial design with no-equivalent control group between subjects, which students answered two questionnaires about their partners’ prosocial behaviour and class climate. The results show a significant differences in favour of the experimental group in the increase of the prosocial individual behaviour and in the collective perception of the atmosphere of the classroom as for the help to subjects with physical problems (p< .001), the positive valuation of the work of others and specially of his actions (p= .007), and it brings over the approximation towards the companions alone or isolated (p = .007).